Factors Associated with the Occurrence of Diarrhea in Babies Under Five Years Old in the Public Health Center Kebun Kopi Jambi City - Marlian Yuniati; Dwi Noerjoedianto; Silvia Mawarti Perdana (Journal of International Multidisciplinary Research, 2024)
Diarrhea is an infection of the digestive tract that poses a global health challenge, including in Indonesia. It is characterized by defecation occurring three or more times in children, or more than four times in neonates within 24 hours, with stools that are soft or liquid, and sometimes contain blood. The incidence of diarrhea at the Kebun Kopi Health Center is particularly high. This study aims to analyze the factors related to the incidence of diarrhea in the working area of the Kebun Kopi Community Health Center, Jambi City. The research utilized a cross-sectional study design, with a population of 843 people, from which 71 samples were selected through accidental sampling. Data were collected through observation and questionnaires, and analyzed univariately and bivariately using the chi-square test. The results indicate a significant relationship between latrine ownership (p-value 0.000), hand washing behavior (p-value 0.000), and knowledge (p-value 0.000) with the incidence of diarrhea. The variables associated with the incidence of diarrhea at the Kebun Kopi Health Center in Jambi City include latrine ownership, hand washing behavior, and knowledge. The high incidence of diarrhea is closely linked to inadequate sanitation, poor hand washing practices, and low levels of health knowledge. To significantly reduce the incidence of diarrhea, it is essential to improve access to proper sanitation, promote effective hand washing practices, and enhance public knowledge about essential health practices.